Docking Studies and Biological Evaluation of a Potential β-Secretase Inhibitor of 3-Hydroxyhericenone F from Hericium erinaceus - Diling, Chen; Tianqiao, Yong; Jian, Yang; Chaoqun, Zheng; Ou, Shuai; Yizhen, Xie (Frontiers in Pharmacology, 2017)
Alzheimer’s disease (AD) is the most common neurodegenerative disorder, affecting approximately more than 5% of the population worldwide over the age 65, annually. The incidence of AD is expected to be higher in the next 10 years. AD patients experience poor prognosis and as a consequence new drugs and therapeutic strategies are required in order to improve the clinical responses and outcomes of AD. The purpose of the present study was to screen a certain number of potential compounds from herbal sources and investigate their corresponding mode of action. In the present study, the learning and memory effects of ethanol:water (8:2) extracts from Hericium erinaceus were evaluated on a dementia rat model. The model was established by intraperitoneal injection of 100 mg/kg/d D-galactose in rats. The results indicated that the extracts can significantly ameliorate the learning and memory abilities. Specific active ingredients were screened in in vivo assays and the results were combined with molecular docking studies. Potential receptor-ligand interactions on the BACE1-inhibitor namely, 3-Hydroxyhericenone F (3HF) were investigated. The isolation of a limited amount of 3HF from the fruit body of H. erinaceus by chemical separation was conducted, and the mode of action of this compound was verified in NaN3-induced PC12 cells. The cell-based assays demonstrated that 3HF can significantly down-regulate the expression of BACE1 (p<0.01), while additional AD intracellular markers namely, p-Tau and Aβ1-42 were further down-regulated (p<0.05). The data further indicate that 3HF can ameliorate certain mitochondrial dysfunction conditions by the reversal of the decreasing level of mitochondrial respiratory chain complexes, the calcium ion levels ([Ca2+]), the inhibiton in the production of ROS, the increase in the mitochondrial membrane potential and ATP levels, and the regulation of the expression levels of the genes encoding for the p21, COX I, COX II, PARP1 and NF-κB proteins. The observations suggest the use of H. erinaceus in traditional medicine for the treatment of various neurological diseases and render 3HF as a promising naturally occurring chemical constituent for the treatment of AD via the inhibition of the β-secretase enzyme.